The Mentality Stated in the Speech (According to the Materials of Ethnographic Expeditions of Adjara) - Shavianidze, Davit (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2020)
We will discuss the issue of the surviving national mentality in Adjara based on the research of toponyms, ethnographic vocabulary, and words found during ethnographic expeditions in the Mareti and Khikhani valleys. We will compare Adjara material with what has already been confirmed in scientific literature written by researchers at different times. The research shows that: A.During the Turkish rule, social psychology defined what Adjarans would get used to, what they did not, and what they would get used to ostensibly; B. Toponyms reflecting Christian and Kartvelian-cultural values played an important role in national survival. („Kunti Jvari“; „St. Seri“; „Ziareti“; „Mother’s Flight“),Vocabulary units, words („Kvakatsebi“; „Pig Tax“; „Gurji“; „I am going to Georgia“; „Topali“; „Khalkhami“; „Tavan Begeli“). The novelty of the „stones“ is that they strengthened the strong character and psychology of the locals in Adjara; The function of the road marking of these niches is the basis for considering the term „Mebodziri“ used to denote the name of the common Georgian „road junction“. Confirmation of Georgian-national ethnopsychology, worldview-surviving views in Adjara: recognition of the vine by the people of Adjara as a „Georgian identity card“; „Dedabodze“ // „Burji“ will be identified with „Gurji“; To say - „I am going to Georgia“, to get rid of ethnic understanding. An example of this is the terms: „Topal“, „Khalkhami“ and „Pig Tax“. It is a fact that in Adjara, too, the fullness of „Tavani“ and „Begeli“ marked the existence of a „soul“ / „living being“. It is important from the functional-social point of view of the completeness of the „head-barn“ to stand as a „barn-chorus“ confirmed in the rest of Georgia. It can be confirmed that: in Adjara, the mentality, the way of life has never been completely changed from Georgian, the values have not disappeared. The desire of the locals to preserve the national was always accompanied by a sense of ownership of the original culture, a willingness to preserve it.